Locality and the order of acquisition steps - van Kempen, Jacqueline (Proceedings of the Amsterdam Colloquium, 2005)
Abstract Preferably, the properties of grammar can be derived from the following factors: (i) The primary linguistic data as they are offered to the child. (ii) A language acquisition procedure. Hopefully, the language acquisition procedure will be compatible with plausible assumptions about the neural abilities of human beings, but that is of no immediate concern. The interaction of the primary data and the acquisition procedure can be studied by a closer look at the order of the child’s acquisition steps. What does she acquire first and why? What does she acquire later and why? My main point will be that this is empirically a promising and by no means trivial approach. At the same time, I will argue against an assumption that is quite common in computational studies and also in mere grammatical studies of child language. People from Gold (1967) to Yang (2002) assume that the acquisition procedure has simultaneous access to all data at once. My point will rather be that the acquisition procedure implies a natural selection of data. The data selection procedure must predict the actual order of the acquisition steps in the various languages.